Desarrollo de un sistema informático para la administración de proyectos realizados dentro del Ministerio de Inclusión Económica y Social (MIES) de la ciudad de Loja. - Lalangui Jaramillo, Yandri José (2011)
The Information Systems have changed the way organizations operate today. Through its use are achieved important changes, as they automate business processes, providing a platform of information needed for decision-making and, the most importantly, its implementation achieves competitive advantage. Over the next few years, the information systems should help to fulfill the following objectives: Automate business processes, provide information to support decision making, archieve competitive advantage through its implementation and use. This is why our research is aimed to provide a solution that contributes to the integration of project information held in each of the programs that make up the Ministry of Economic and Social Inclusion (MIES) City Loja, allowing to have established a database with relevant information to achieve effectiveness in the control and monitoring of projects, helping to effectively and efficiently to the timely decision making for the better development of the processes that require managing projects results that meet the managers and beneficiaries of these.